2022
DOI: 10.1371/journal.pone.0272498
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbid severe mental illness and common chronic physical health conditions on hospitalisation: A systematic review and meta-analysis

Abstract: Background People with severe mental illness (SMI) are at higher risk of physical health conditions compared to the general population, however, the impact of specific underlying health conditions on the use of secondary care by people with SMI is unknown. We investigated hospital use in people managed in the community with SMI and five common physical long-term conditions: cardiovascular diseases, COPD, cancers, diabetes and liver disease. Methods We performed a systematic review and meta-analysis (Prospero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…These findings corroborate established evidence on mental-somatic comorbidity,3 4 10 12–18 accentuating the essentiality for hospitals to address these challenges comprehensively, ensuring superior care for affected patients.…”
Section: Introductionsupporting
confidence: 81%
“…These findings corroborate established evidence on mental-somatic comorbidity,3 4 10 12–18 accentuating the essentiality for hospitals to address these challenges comprehensively, ensuring superior care for affected patients.…”
Section: Introductionsupporting
confidence: 81%
“…Previous systematic reviews and studies have shown that people with SMI have more chronic physical illnesses, and these comorbidities have a worse prognosis than those in the general population [4,3,[32][33][34]. The comorbid chronic physical diseases of patients with SMI cause many different problems.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and the mental states are inextricably linked, and their separation can lead to health inequalities and a lack of appropriate holistic care, especially for the most vulnerable patients. Poor mental health results in more frequent hospitalization for somatic diseases [24,25]. On the other hand, the physical condition plays an important role in perceived well-being [26,27]; for example, depression is two to three times more common in people with chronic physical illnesses than in people who have good physical health [28].…”
Section: Discussionmentioning
confidence: 99%